Beyond NAMs versus animal models: Context of use as the governing framework for integrated nonclinical strategies in drug development - Stefano Gaburro; Brian Berridge; Nicholas W. Kelley; Eckhard von Keutz; Marc Ferrer; Clive Roper; Michael J. Fossler; Jeffrey J. Bajramovic; Jean-Pierre Valentin; Timothy McGovern; Todd Bourcier; Ronald L. Wange; et al. (Regulatory Toxicology and Pharmacology, 2026)

The Wolverine Project: Evaluating Cumulative Effects Within the Land of Ktunaxa Using the One Heart Method - Nikki Heim; Ryan MacDonald; Christopher Horsethief; Chad Luke; Michael Proctor; Marlene Machmer; Vi Birdstone; Ray Warden; Curtis Wullum; Rachel Plewes; Matthew Chernos; Matt Carlson (Environmental Management, 2025)

Gene flow prevents genetic diversity loss despite small effective population size in fragmented grizzly bear (Ursus arctos) populations - Megan F. Turnock; Justin E. Teisberg; Wayne F. Kasworm; Matthew R. Falcy; Michael F. Proctor; Lisette P. Waits (Conservation Genetics, 2025)
Genetic monitoring is important in small, fragmented populations that rely on gene flow to maintain genetic diversity. The Selkirk, Yaak, and Cabinet grizzly bear ( Ursus arctos ) populations are among the smallest in North America and are near the southernmost extent of the species’ range. These populations received little to no effective migration for generations but have recently experienced increased gene flow through natural migration and a population augmentation program. A long-term dataset of grizzly bear microsatellite genotypes from 1973 to 2021 presented a unique opportunity to examine genetic trends in these populations over time. We used this dataset of 464 bears to evaluate if gene flow affected observed heterozygosity ( H O ), expected heterozygosity ( H E ), allelic richness ( A R ), and average pairwise relatedness ( r ) in each of these populations. We also estimated effective population size ( N e ) using the temporal and linkage disequilibrium (LD) methods. Post gene flow, A R increased in the Selkirk and Cabinet populations and r decreased in all three populations. We did not observe any significant changes in H E or H O , but H E values in our populations were significantly higher than those estimated using a model without gene flow. Our N e estimates were consistent between the temporal and LD methods and ranged from 15.2 to 15.8, 15.4–17.5, and 5.6–8.9 for the Selkirk, Yaak, and Cabinet populations, respectively. Overall, our findings indicate that gene flow is increasing or maintaining genetic diversity in these populations. However, N e remains low and additional connectivity or augmentation may be needed, particularly in the Cabinet population.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Corridor‐based approach with spatial cross‐validation reveals scale‐dependent effects of geographic distance, human footprint and canopy cover on grizzly bear genetic connectivity - Eric C. Palm; Erin L. Landguth; Zachary A. Holden; Casey C. Day; Clayton T. Lamb; Paul F. Frame; Andrea T. Morehouse; Garth Mowat; Michael F. Proctor; Michael A. Sawaya; Gordon Stenhouse; Jesse Whittington; et al. (Molecular Ecology, 2023)
Understanding how human infrastructure and other landscape attributes affect genetic differentiation in animals is an important step for identifying and maintaining dispersal corridors for these species. We built upon recent advances in the field of landscape genetics by using an individual‐based and multiscale approach to predict landscape‐level genetic connectivity for grizzly bears ( Ursus arctos ) across ~100,000 km 2 in Canada's southern Rocky Mountains. We used a genetic dataset with 1156 unique individuals genotyped at nine microsatellite loci to identify landscape characteristics that influence grizzly bear gene flow at multiple spatial scales and map predicted genetic connectivity through a matrix of rugged terrain, large protected areas, highways and a growing human footprint. Our corridor‐based modelling approach used a machine learning algorithm that objectively parameterized landscape resistance, incorporated spatial cross validation and variable selection and explicitly accounted for isolation by distance. This approach avoided overfitting, discarded variables that did not improve model performance across withheld test datasets and spatial predictive capacity compared to random cross‐validation. We found that across all spatial scales, geographic distance explained more variation in genetic differentiation in grizzly bears than landscape variables. Human footprint inhibited connectivity across all spatial scales, while open canopies inhibited connectivity at the broadest spatial scale. Our results highlight the negative effect of human footprint on genetic connectivity, provide strong evidence for using spatial cross‐validation in landscape genetics analyses and show that multiscale analyses provide additional information on how landscape variables affect genetic differentiation.

Range‐wide evolutionary relationships and historical demography of brown bears ( Ursus arctos ) revealed by whole‐genome sequencing of isolated central Asian populations - Odbayar Tumendemberel; Sarah A. Hendricks; Paul A. Hohenlohe; Jack Sullivan; Andreas Zedrosser; Mona Sæbø; Michael F. Proctor; John L. Koprowski; Lisette P. Waits (Molecular Ecology, 2023)
Phylogeographic studies uncover hidden pathways of divergence and inform conservation. Brown bears ( Ursus arctos ) have one of the broadest distributions of all land mammals, ranging from Eurasia to North America, and are an important model for evolutionary studies. Although several whole genomes were available for individuals from North America, Europe and Asia, limited whole‐genome data were available from Central Asia, including the highly imperilled brown bears in the Gobi Desert. To fill this knowledge gap, we sequenced whole genomes from nine Asian brown bears from the Gobi Desert of Mongolia, Northern Mongolia and the Himalayas of Pakistan. We combined these data with published brown bear sequences from Europe, Asia and North America, as well as other bear species. Our goals were to determine the evolutionary relationships among brown bear populations worldwide, their genetic diversity and their historical demography. Our analyses revealed five major lineages of brown bears based on a filtered set of 684,081 single nucleotide polymorphisms. We found distinct evolutionary lineages of brown bears in the Gobi, Himalayas, northern Mongolia, Europe and North America. The lowest level of genetic diversity and the highest level of inbreeding were found in Pakistan, the Gobi Desert and Central Italy. Furthermore, the effective population size ( N e ) for all brown bears decreased over the last 70,000 years. Our results confirm the genetic distinctiveness and ancient lineage of brown bear subspecies in the Gobi Desert of Mongolia and the Himalayas of Pakistan and highlight their importance for conservation.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Water safety attitudes, risk perception, experiences, and education for households impacted by the 2018 Camp Fire, California - Tolulope O. Odimayomi; Caitlin R. Proctor; Qi Erica Wang; Arman Sabbaghi; Kimberly S. Peterson; David J. Yu; Juneseok Lee; Amisha D. Shah; Christian J. Ley; Yoorae Noh; Charlotte D. Smith; Jackson P. Webster; et al. (Natural Hazards, 2021)

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Microclimate, light adaptation and desiccation tolerance of epiphytic bryophytes in two Venezuelan cloud forests - Yelitza León‐Vargas; Stefan Engwald; Michael C. F. Proctor (Journal of Biogeography, 2006)
Aim Analysis of microclimate factors and physiological responses determining survival and growth of epiphytic bryophytes in the lower canopy and trunk space of north‐Andean cloud forests. Location Two cloud forests at 2000–2400 m in the northern Andes near Mérida, Venezuela. Methods Data‐logging of dry and wet‐season temperature, relative humidity (r.h.) and photosynthetically‐active radiation (PAR) for month‐long periods, and laboratory measurements of desiccation tolerance and light responses of selected epiphytic bryophytes. Results Rainfall averages 20 mm or less in January and February, and 200 mm or more from August to October, but is very variable at all seasons. The proportion of time ‘wet’ (continuous 100% r.h.) in the months sampled ranged from 8.5% to 52.2% or more; a dry/wet‐season range between 20% and 40% is probably commoner. The length of ‘wet’ and ‘dry’ periods approximated log‐normal distributions, with mid‐points for wet periods ranging from 2.8 to 10.7 h, and dry periods from 6.2 to 17.1 h. The longest recorded dry period was 143 h. Humidity typically rose during the night to > 90% r.h., reaching 100% for significant periods (implying cloudwater (fog) deposition) on about one night in two in all seasons. Of six bryophytes of pendulous growth form, all survived periods of at least a few days’ desiccation; most recovered better from high than low humidities. Measured 95% light‐saturation values ranged from 110 to 256 μ mol m −2 s −1 , somewhat but not greatly higher than ambient light levels Main conclusions Environmental conditions in the cloud forests are probably near‐optimal for epiphytic bryophytes, but in even the wettest forest these plants must tolerate at least short periods of drying at any time of year, and longer periods seasonally. Interception of cloudwater droplets from moving air is likely to be an important source of water for bryophytes of pendant and other diffuse life forms, especially in periods of low rainfall. Absorption of water from near‐saturated air is probably of little physiological significance. Bryophytes of these life‐forms are notably conspicuous in tropical‐montane cloud forests. They remain prominent into humid temperate regions such as southern Chile, New Zealand and Macaronesia, but progressively disappear at higher latitudes with the stresses of increasing seasonality.

Early morning photosynthesis of the moss Tortula ruralis following summer dew fall in a Hungarian temperate dry sandy grassland - Zsolt Csintalan; Zoltán Takács; Michael C.F. Proctor; Zoltán Nagy; Zoltán Tuba (Plant Ecology, 2000)

The bryophyte paradox: tolerance of desiccation, evasion of drought - Michael C.F. Proctor (Plant Ecology, 2000)

Nitrogen fixation by achromobacter spp. - Michael H. Proctor; P. W. Wilson (Archives of Microbiology, 1959)